SYNTHESIS AND CHARACTERIZATION OF TRANSITION METALCOMPLEXES OF 2-THIOACETIC ACID BENZOTHIAZOLE LIGAND - Majeed, Ahmed; Yousif, Emad; Farina, Yang (Al-Nahrain Journal of Science, 2010)
New metal complexes of the ligand 2-thioacetic acid benzothiazole with the metal ions Fe(III), Rh(III), Pd(II), Pt(IV) and Au(III) were prepared in alcoholic medium.The prepared complexes were characterized by FTIR Spectroscopy, electronic spectroscopy, elemental analysis, 1HNMR, 13C NMR, magnetic susceptibility and conductivity measurements. Molar ratio and continuous variation studies in solution gave comparable result with those obtained from solid state study. From the spectral measurements, monomer structures for the complexes were proposed.